Wrist impact during the execution of hip circles on the pommel horse in gymnastics - Ferrer, V.; Turmo, A. (Archivos de medicina del deporte, 2008)
Men`s gymnastics is comprised of six events, all of them produce loadings to the upper limb. The pommel horse demands repetitive and high intensity wrist impacts on a rigid structure (mean overall loading rate ranged between 5,3 BW/s to 10,6 BW/s), with sustained periods of body weight support on the wrist (Marklof, et al. 1990). The purpose of this study was to analyse the impacts and the loading rate received by the gymnasts during the execution of circles on a mushroom apparatus, used to improve techniques of the pommel horse. Method: We established four phases for a complete circle on the mushroom, two double support phases (Phases A and C) and two single support phases (Phases B and D). Four male gymnasts of the national team, one Olympic level and three junior international level, performed two series of ten circles on the mushroom. The mushroom was placed over a force platform at a sample rate of 1000hz. Performance was recorded with one high speed camera with a sample rate of 200hz and another one at 50hz. The event was captured at the same time on the force platform with high resolution cameras to synchronize the data collection prior to the performance. Results: Gymnasts of the study took a mean of 0.927 ± 0.032 seconds to do a circle, and spent 72% of the time during single supports and 28% during double supports. The resultant force increased to maximum values of 1.77 ± 0.17 BW, always on the arrival of carpus on double support phases, and showed a mean loading rate of 10.66 BW/s. Impulse during single support phases was 0,15 x BW higher than in double supports. In the instant of maximal lateral forces (single supports) gymnasts demonstrated an average wrist extension of 86,3 ± 4,0º. Discussion/Conclusions: As the young gymnasts execute hip circles on the mushroom to learn specific skills of pommel horse during the learning period, concomitant to the growth period, and those exercises produce important impacts, high loading rates and risky angles of extension of the wrist has been observed in our study. We postulate that the impact of the time loading depending on the maturation process of the athlete and a clinical evaluation of the wrist (signs, symptoms and complementary tests) had to be taken into account on the evolution of the athlete